The Archive of University of Valencia, a research tool - Manclús Cuñat, Mª Irene (CIAN-Revista de Historia de las Universidades, 2013)
This article is focused on the importance of university archive for understanding the history of the institution. In order to know the history of this university it is necessary to use the files and the materials hold in the archives of the University. With this article we try to enter into the knowledge of the University of Valencia through their “roles” in your file, showing the wealth amassed from his as definite character and history of more than five hundred years.
Keywords: Archive; University of Valencia; History of the University